Partnership Agreement PT. Go-Jek Indonesia In View of Civil Code of Law - ANNISA RIZQI PRADANI (Authentica, 2021)
PT. GO-JEK Indonesia gives a fresh breeze to the base motorcycle taxis who just sit and wait for passengers to be able to join as partners, the drivers must cooperate with the company. The cooperation is expressed in the form of a partnership agreement. The problem occurs because the driver does not understand the partnership agreement and raises the impression of imbalance between the parties, the driver demands to be made an employee or worker. This research aims to analyze PT partnership agreement. GO-JEK Indonesia with drivers is reviewed according to the Civil Code. This research uses normative juridical approach methods to analyze partnership agreements as what is written in the legislation.  Partnership agreements made by PT. GO-JEK Indonesia and drivers comply with Article 1313 of the Civil Code and have fulfilled the legal element of article 1320 of the Civil Code both subjective and objective requirements. Partnership agreements made in formil are written in black and white and made electronically (online). The partnership agreement contains detailed reciprocal agreements containing the rights and obligations of each of the parties. Partnership agreements are a type of nameless agreement whose rules are subject to the general rules of chapters I, II,IV of book III, and the principle of freedom of contract. Elements of the partnership agreement differ from the elements of the employment agreement. Keywords: Agreements, Partnership Agreements, PT. GO-JEK Indonesia